2016
DOI: 10.1038/nature18954
|View full text |Cite
|
Sign up to set email alerts
|

eIF3d is an mRNA cap-binding protein that is required for specialized translation initiation

Abstract: Eukaryotic mRNAs contain a 5' cap structure critical for recruitment of the translation machinery and initiation of protein synthesis. mRNA recognition is thought to require direct interactions between eukaryotic initiation factor 4E (eIF4E) and the mRNA cap. However, translation of numerous capped mRNAs remains robust during cellular stress, early development, and cell cycle progression1 despite eIF4E inactivation. Here we describe a new cellular cap-dependent pathway of translation initiation that relies on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
377
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 303 publications
(391 citation statements)
references
References 34 publications
13
377
1
Order By: Relevance
“…Reduction in eIF3d levels prevented translational recovery during chronic ER stress (Figure 4D), while not altering the effects of Tg or PERKi on eIF2B activity (Figure 4G). Consistent with earlier observations that eIF3d can selectively affect translation (Lee et al, 2016), depletion of eIF3d strongly inhibited polysomal association of the ATF4 mRNA even in unstressed cells (Figures S3E vs. 1D), but had only a marginal effect on GADD34 mRNA translation (Figures S3E vs. S2). Furthermore, the eIF3d-RNA co-immunoprecipitation experiments revealed a decrease in association of eIF3d with mRNAs that are translationally repressed ( e.g.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…Reduction in eIF3d levels prevented translational recovery during chronic ER stress (Figure 4D), while not altering the effects of Tg or PERKi on eIF2B activity (Figure 4G). Consistent with earlier observations that eIF3d can selectively affect translation (Lee et al, 2016), depletion of eIF3d strongly inhibited polysomal association of the ATF4 mRNA even in unstressed cells (Figures S3E vs. 1D), but had only a marginal effect on GADD34 mRNA translation (Figures S3E vs. S2). Furthermore, the eIF3d-RNA co-immunoprecipitation experiments revealed a decrease in association of eIF3d with mRNAs that are translationally repressed ( e.g.…”
Section: Resultssupporting
confidence: 91%
“…Under specific conditions, it has been reported that eIF3 may directly bind a subset of mRNAs and recruit them to the 43S complex in an eIF4F-independent manner (Lee et al, 2015; Lee et al, 2016). We therefore tested whether selected eIF3 subunits show differential binding to mRNAs in control vs. chronically stressed cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…230 This model was based on the assumption that cap recognition is always mediated by eIF4E, but this assumption has been disproven by important studies that demonstrate that eIF3D, a subunit of the eIF3 protein complex, can recognize the cap and mediate cap-dependent translation initiation in some mRNAs with structured 5′UTRs. 231 We propose that DENV2 employs noncanonical mechanisms to mediate cap-dependent translation initiation, possibly via direct recruitment of the eIF3 complex.…”
Section: Biochemistry and Molecular Biology Of Flavivirusesmentioning
confidence: 96%